VD_FINDINFO HC / 2011 / 333 vom 7. Juni 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE | 176 al. 1 ch. 1 CC, 176 al. 3 CC, 276 CC, 308 al. 1 let. b CPC (CH), 317 al. 1 CPC (CH)